2020
DOI: 10.1186/s12933-020-01009-4
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on alternative non-classical mechanisms of PCSK9 in atherosclerosis in patients with and without diabetes

Abstract: The proprotein convertase subtilisin/kexin type 9 (PCSK9) acts via a canonical pathway to regulate circulating lowdensity lipoprotein-cholesterol (LDL-C) via degradation of the LDL receptor (LDLR) on the liver cell surface. Published research has shown that PCSK9 is involved in atherosclerosis via a variety of non-classical mechanisms that involve lysosomal, inflammatory, apoptotic, mitochondrial, and immune pathways. In this review paper, we summarized these additional mechanisms and described how anti-PCSK9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…A genetic reduction of PCSK9 levels by 50% is associated with a similar percent reduction of coronary heart disease (CHD) risk [ 59 ] and a genetic large-scale study on 337,536 individuals of British ancestry reported that the rs11591147 PCSK9 mutation had a protective effect not only on hyperlipidemia, but also on the risk of CHD (− 27%) and ischemic stroke (− 39%) [ 60 ]. A further hypothesis linking PCSK9 to atherosclerosis is the direct role that this protein can play on atherogenesis (reviewed in [ 61 ]). Indeed, PCSK9, expressed in vascular smooth muscle cells, human atherosclerotic plaques and epicardial adipose tissue [ 62 ], reduces macrophage cholesterol efflux capacity, raises the migratory ability of monocytes and the expression of scavenger receptors, thus enhancing ox-LDL uptake in monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic reduction of PCSK9 levels by 50% is associated with a similar percent reduction of coronary heart disease (CHD) risk [ 59 ] and a genetic large-scale study on 337,536 individuals of British ancestry reported that the rs11591147 PCSK9 mutation had a protective effect not only on hyperlipidemia, but also on the risk of CHD (− 27%) and ischemic stroke (− 39%) [ 60 ]. A further hypothesis linking PCSK9 to atherosclerosis is the direct role that this protein can play on atherogenesis (reviewed in [ 61 ]). Indeed, PCSK9, expressed in vascular smooth muscle cells, human atherosclerotic plaques and epicardial adipose tissue [ 62 ], reduces macrophage cholesterol efflux capacity, raises the migratory ability of monocytes and the expression of scavenger receptors, thus enhancing ox-LDL uptake in monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The best-known function of PCSK9 is posttranslational regulation of LDLR on hepatocytes, which is the major route for LDL-C clearance from the circulation. In addition to from the canonical pathway, PCSK9 regulates lipid metabolism by intracellular endogenous PCSK9-induced LDLR degradation, VLDLR degradation, regulation of apolipoprotein B secretion, and lipoprotein(a) metabolism [ 5 , 22 ]. PCSK9 is also associated with macrophage cholesterol efflux, apoptosis of endothelial cells, mitochondrial dysfunction, and inflammation [ 5 ], which contribute to metabolic disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to from the canonical pathway, PCSK9 regulates lipid metabolism by intracellular endogenous PCSK9-induced LDLR degradation, VLDLR degradation, regulation of apolipoprotein B secretion, and lipoprotein(a) metabolism [ 5 , 22 ]. PCSK9 is also associated with macrophage cholesterol efflux, apoptosis of endothelial cells, mitochondrial dysfunction, and inflammation [ 5 ], which contribute to metabolic disturbance. Furthermore, we found that PCSK9 was positively associated with ALT, AST, and GGT [ 23 ], liver function indices that are known as sensitive indicators of liver dysfunction and hepatic insulin resistance in diabetes [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A genetic reduction of PCSK9 levels by 50% is associated with a similar percent reduction of coronary heart disease (CHD) risk [59] and a genetic large-scale study on 337,536 individuals of British ancestry reported that the rs11591147 PCSK9 mutation had a protective effect not only on hyperlipidemia, but also on the risk of CHD (-27%) and ischemic stroke (-39%) [60]. A further hypothesis linking PCSK9 to atherosclerosis is the direct role that this protein can play on atherogenesis (reviewed in [61]). Indeed, PCSK9, expressed in vascular smooth muscle cells, human atherosclerotic plaques and epicardial adipose tissue [62], reduces macrophage cholesterol e ux capacity, raises the migratory ability of monocytes and the expression of scavenger receptors, thus enhancing ox-LDL uptake in monocytes and macrophages.…”
Section: Depressionmentioning
confidence: 99%